INTEGRATED NATURAL RUBBER AGROINDUSTRY DEVELOPMENT MODEL - Fahmi Riadi, Machfud, Tajuddin Bantacut dan Illah Sailah (Jurnal Teknologi Industri Pertanian, 2011)
ABSTRACTAgoindustrial development is very strategic when it is integrated and sustainably managed, i.e. there’s linkage among upstream and downstream sectors sinergically, productively, and also linkage among regionals, sectors and commodities.  This study was  aimed to find an integrated and sustainable model for developing of natural rubber agroindustry. Among the constraints of agroindustrial development were  small scale of agro-processing units and separated location to gain the sufficient operation scale.  Development factors gained from the experts judgment aggregated using pair wise comparation technique and Analytical Hierarchy Process (AHP). Institutions and development constraints were analyzed using Interpretive Structural Modeling (ISM) technique.   Integration of every stage of business activities vertically showed that improvement  of all feasibility indicators, such as NPV, IRR, Net B/C, and PBP significantly and also saved total investments. This study concludes that contract farming model and rubber agroforestry system-1 were preferred and more profitable for the agroindustrial development based on latex and rubberwood.  Besides that, the farmers have  a chance to participate and  invest their capitals, even playing the main role in the project.  Keywords: agroindustry, integration, sustainable, natural rubber, partnership